Efektivitas Pengelolaan Anggaran Tahun 2021 terhadap Capaian Kinerja Dinas Pemberdayaan Perempuan Perlindungan Anak dan Keluarga Berencana (DP3AKB) Kabupaten Aceh Barat - Hilda Ameliya; Cut Asmaul Husna (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This article aims to find out how the effectiveness of budget management in 2021 on the performance achievements of the women's empowerment agency, child protection and family planning in West Aceh Regency, in implementing budget management for an agency to make it easier to complete an activity or program that is being carried out with the existing budget. This budget preparation guide refers to government regulations and is guided by the DPA, in managing this budget DP3AKB cooperates with BAPPEDA and BPKD Aceh Barat Regency. This research uses a qualitative method with a descriptive approach, then the data collection is done by interview, observation and documentation, the data taken by the researcher is data from the Financial Report, LAKIP and DP3AKB Work Plan. The results of the study explain that the effectiveness of budget management is not yet fully effective, because there is still a lack of adequate human resources.